2021
DOI: 10.1177/09544062211038981
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigations on the effect of target thickness and solution treatment on the ballistic behaviour of AA7075 thick plates

Abstract: The influence of target thickness and solution treatment on the ballistic behaviour of AA7075 targets has been investigated by both numerical and experimental methods. In numerical simulation, the target thickness was varied from 19 to 26 mm and an Ogive nose shaped projectile of 7.62 mm diameter with inlet velocities ranging between 800–875 m/s was considered. In order to justify the numerical observations, high velocity ballistic experiments were conducted on AA7075-T651 and the solution treated plates of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…DIC was found to be a valuable tool for comparing the deformation response of different welding techniques. Praveen et al (2022) conducted numerical and experimental investigations to study the ballistic behavior of AA7075 thick plates under different target thicknesses and solution treatments [ 76 ]. The results showed that the solution treatment improved the BR of the plates, and thicker plates exhibited better ballistic performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DIC was found to be a valuable tool for comparing the deformation response of different welding techniques. Praveen et al (2022) conducted numerical and experimental investigations to study the ballistic behavior of AA7075 thick plates under different target thicknesses and solution treatments [ 76 ]. The results showed that the solution treatment improved the BR of the plates, and thicker plates exhibited better ballistic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Damage criteria are also crucial for obtaining reliable numerical ballistic results [22]. It was discovered that the correlation between experimental and numerical ballistic impact analysis of two distinct heat treated AA7075 aluminium alloy targets was stronger [23][24][25]. The vast majority of research on AA5083 targets [8,9] has been conducted using thin sheets and single hits.…”
Section: Introductionmentioning
confidence: 99%
“…Precise control of film thickness reduces the paint consumption. [50][51][52] The variations in film thickness for normal paint material and different MWCNT-based nanopaint are plotted in Figure 8. It is observed that there is a decrease of 3.1% in film thickness when compared with 0.5 gm of MWCNT nanopaint and a 3.4% decrease than normal painting thickness.…”
Section: Effect Of Thickness Of the Coating By Robot Paintingmentioning
confidence: 99%
“…A group of researchers investigated the ballistic response of aluminium 7xxx grades at higher impact velocity projectiles using experimental, theoretical and numerical studies. 12,13 By using the friction stir processing approach, 14,15 the ballistic performance of B 4 C reinforced AA7075 target was investigated. They reported that adding boron carbide and molybdenum disulphide to the surface of the aluminium alloy 7075 target surface improved its wear and ballistic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the literature has dealt with a variety of numerical and experimental ballistic studies on composite materials, surface modifications, reinforcement of metal matrix composites, different kinds of projectiles and their shapes, optimized ballistic limit velocities, and friction stir process plates. [1][2][3][4][5][6][7][8][9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Furthermore, there are numerous reports in the literature on the high-velocity impact of various Al alloys; a comprehensive study on the projectile's penetration behaviour in single layered rolled condition plates of various thicknesses and heat treatments are needed. As a result, the specified condition of heat treatment and optimized target thickness necessary to prevent complete penetration can be chosen.…”
Section: Introductionmentioning
confidence: 99%